Phytochemical test fraction N-hexane allelopathy goat weed extracts (Ageratum conyzoides L.) on the growth of thorn spinach (Amarantus spinosus L.). Issue 1 (January 2020) - Nandi, M V P; Hasanuddin,; Hafsah, S
Abstract: Plants release allelopathy compounds that can inhibit the growth of other plants so that it has the potential as a vegetable herbicide. One of the allelopathy characters that can be used in determining the criteria as a basis for plant biocides is allelopathy that specifically inhibits the growth of target and non-target plants. The source of allelopathy used in this study was goat weed ( A. conyzoides ) using N-hexane on the growth of thorn spinach ( A. spinosus ). The research has been carried out at Weed Laboratory, Agrotechnology Study Program, Faculty of Agriculture, Syiah Kuala University. Further analysis and test activities were carried out at the Laboratory of Agriculture and Food Analysis Laboratory of the Faculty of Agriculture, Syiah Kuala University. The first factor was the type of sub-fraction of weed extract consisting of 4 levels: control, sub-fraction A, sub-fraction B and sub-fraction C, and the second factor is the extract of goat weed consisting of 3 levels: 5%, 10% and 15%. The results showed that the use of various types of A. conyzoides extracts with various levels significantly affected the stem diameter; shoot dry weight and root dry weight of A. spinous on 7 DAT (days after treatment) up to 28 DAT. Sub-fraction types A and B can inhibit the growth of A. spinous . A post-publication change was made to this article on 11 Mar 2020 to correct the conference title in the PDF header.